2020
DOI: 10.1182/blood.2019003886
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab treatment of relapsed/refractory Epstein-Barr virus–associated hemophagocytic lymphohistiocytosis in adults

Abstract: Epstein-Barr virus (EBV)-associated hemophagocytic lymphohistiocytosis (EBV-HLH) is a life-threatening hyperinflammatory syndrome triggered by EBV infection. It often becomes relapsed or refractory (r/r), given that etoposide-based regimens cannot effectively clear the virus. r/r EBV-HLH is invariably lethal in adults without allogeneic hematopoietic stem cell transplantation. Here, we performed a retrospective analysis of 7 r/r EBV-HLH patients who were treated with nivolumab on a compassionate-use basis at W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 29 publications
2
74
0
Order By: Relevance
“…Stressing the relevance of possibly exhausted CD8 + T cell functions in the uncontrolled monocyte activation and cytokine release syndrome, Liu et al ., recently described how systemic PD-1 blockade could mitigate the hemophagocytic lymphohistiocytosis (HLH) syndrome in patients suffering from EBV-induced HLH. 197 In EBV-induced HLH, single-cell RNA-sequencing analysis revealed that HLH syndrome was associated with hyperactive monocytes/macrophages (expressing high levels of CD163, IL-1β, IL-6) and ineffective CD8 + T cell response characterized by a defective activation program (apoptosis, reduced TCR signaling, lower IFNγ/GrzB/Ki67 and higher PD-1/LAG3 exhaustion markers). 197 SARS-CoV2 -induced secondary HLH could be observed in severe cases of COVID-19.…”
Section: The Wrong Side Of the Janus Face: Virus-induced Immunopatholmentioning
confidence: 99%
See 1 more Smart Citation
“…Stressing the relevance of possibly exhausted CD8 + T cell functions in the uncontrolled monocyte activation and cytokine release syndrome, Liu et al ., recently described how systemic PD-1 blockade could mitigate the hemophagocytic lymphohistiocytosis (HLH) syndrome in patients suffering from EBV-induced HLH. 197 In EBV-induced HLH, single-cell RNA-sequencing analysis revealed that HLH syndrome was associated with hyperactive monocytes/macrophages (expressing high levels of CD163, IL-1β, IL-6) and ineffective CD8 + T cell response characterized by a defective activation program (apoptosis, reduced TCR signaling, lower IFNγ/GrzB/Ki67 and higher PD-1/LAG3 exhaustion markers). 197 SARS-CoV2 -induced secondary HLH could be observed in severe cases of COVID-19.…”
Section: The Wrong Side Of the Janus Face: Virus-induced Immunopatholmentioning
confidence: 99%
“… 197 In EBV-induced HLH, single-cell RNA-sequencing analysis revealed that HLH syndrome was associated with hyperactive monocytes/macrophages (expressing high levels of CD163, IL-1β, IL-6) and ineffective CD8 + T cell response characterized by a defective activation program (apoptosis, reduced TCR signaling, lower IFNγ/GrzB/Ki67 and higher PD-1/LAG3 exhaustion markers). 197 SARS-CoV2 -induced secondary HLH could be observed in severe cases of COVID-19. 32 , 198 , 199 …”
Section: The Wrong Side Of the Janus Face: Virus-induced Immunopatholmentioning
confidence: 99%
“…The clinical role of ICIs in EBV-positive DLBCL and EBV-related PTLDs is unknown. Case reports/studies of ICIs in EBV-related PTLD post allogeneic stem cell transplantation and other B-cell EBV lymphoproliferations, such as lymphomatoid granulomatosis and hemophagocytic lymphohistiocytosis [ 97 100 ], suggest a potential role of ICIs in the treatment of such EBV-related diseases. An interesting ongoing clinical trial is evaluating the role of nivolumab monotherapy or in combination with agents or cellular therapies in EBV-positive lymphomas ( Table 3 ).…”
Section: Aggressive B-cell Lymphomasmentioning
confidence: 99%
“…19,20 Several studies have reported that the single-agent anti-PD-1 antibody could provide an ORR of 57.1-100% in r/r NKTL, with a 1-year OS rate of 82.1%. [21][22][23][24][25] Further, those encouraging results on anti-PD-1 antibody in NKTL have started to challenge the current treatment paradigms of NKTL and have provided the rationale for evaluating PD-1 blockade as a firstline therapy of patients with advanced NKTL.…”
Section: Introductionmentioning
confidence: 99%